Cover crop-based reduced tillage system influences Carabidae (Coleoptera) activity, diversity and trophic group during transition to organic production. Issue 6 (10th January 2017) - Rivers, Ariel; Mullen, Christina; Wallace, John; Barbercheck, Mary
Abstract: Organic grain growers rely on cultural practices and biological control to regulate pests, and the implementation and timing of cultural practices can affect many characteristics of the cropping system as a habitat for natural enemies of arthropod pests. Ground beetles (Coleoptera: Carabidae) in particular are important insect and weed-seed predators, and are sensitive to crop rotations, tillage and environmental complexity. In a reduced tillage system in transition to organic management, we evaluated the effect of cover crop species and termination date, crop rotation and high residue cultivation on ground and tiger beetle (Coleoptera: Carabidae) activity-density, community composition and size and trophic groups. The 3-year experiment included a sequence of corn ( Zea mays L.), soybean ( Glycine max (L.) Merr.) and winter wheat ( Triticum aestivum L.). A mixture of hairy vetch ( Vicia villosa Roth) and triticale (x Triticosecale Wittmack) preceded corn, and cereal rye ( Secale cereale L.) preceded soybean, and each crop sequence was present in each year (full-entry). We compared three cover crop termination (and cash crop planting) dates by terminating the overwintered cover crops with a roller-crimper, and immediately or soon after, we no-till planted corn and soybean through the mat created by the rolled cover crops. In the corn and soybean phases of the rotation, we also compared inter-row cultivation as a pest management strategy to a control treatment (no inter-row cultivation in corn, and an alternative row-spacing in soybean). Wheat was planted on a single date in each year into tilled soil. Carabids were sampled using pitfall traps 2 weeks after termination of the two cover crop treatments, and in mid-June in wheat. Carabid activity-density and species richness increased across the experimental site during the 3-year transition, and community evenness across the experimental site increased by the third year. Crop species influenced carabid community composition, and by the third year, the carabid community was comparable between wheat and hairy vetch-triticale cover crop. The late cover crop termination date was positively associated with higher activity-densities of large carabids in rolled hairy vetch-triticale and rolled cereal rye; carnivorous beetles in rolled hairy vetch-triticale; and granivorous beetles in rolled cereal rye. Inter-row cultivation occurring in corn and soybean resulted in a significantly higher proportion of small beetles in the wheat phase of the rotation, with a significantly higher proportion of large beetles in wheat treatments, which had not received inter-row cultivation in corn and soybean. Results have strong implications for management during the transition to organic, including the importance of plant residue, reduced tillage and timing of cover crop termination dates for augmenting carabid populations.